An efficient, fast, and green procedure to quantify α- and β-acids and xanthohumol in hops and their derived products - de Oliveira Sartori, Leonardo [UNESP]; Alves Souza, Amauri [UNESP]; Sanchez Bragagnolo, Felipe [UNESP]; Cassia Fortuna, Gabriel [UNESP]; Pereira Giardini Bonfim, Filipe [UNESP]; Rodrigues Sarnighausen, Valéria Cristina [UNESP]; Lajarim Carneiro, Renato; Soleo Funari, Cristiano [UNESP] (Elsevier, 2022)
The main precursors of bitter principles of beer are α-acids, followed by β-acids. Determination of their content in hop cones and their derivatives is an essential part of brewing. HPLC-UV is the preferred technique when a more precise quantification of some specific bitter acids are required. However, current methods do not allow the proper quantification of all the six major α- and β-acids; furthermore, these multi-step methods generate considerable volumes of chemical waste. In this work, a new UHPLC-UV protocol was developed and compared side-by-side with reference, considering traditional and sustainability parameters. Baseline separations were achieved for the six major bitter acids and xanthohumol, while a greener and faster sample preparation procedure was developed. The new validated procedure could be adopted for quality control of hops and their derivative products with enhanced sample throughput and with a potential gain in the safety of the analyst.
Keywords: Dimethyl carbonate; Extraction; Green analytical chemistry; Sample preparation; UHPLC